Occupational Therapy Interventions and Their Impact on Work Performance and Activities of Daily Living in Persons with Multiple Sclerosis - Denis Arsovski (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Multiple sclerosis (MS) is a chronic neurological disease that affects the central nervous system, leading to various physical, cognitive, and emotional challenges that significantly impact daily activities and work performance. Occupational therapy (OT) plays an important role in managing MS by providing interventions designed to improve functional performance, promote independence, and enhance overall well-being.